The Importance of Self-Care for Healthcare Professionals in North India: A Regional Analysis of Burnout, Resilience and Institutional Support - Atul Khajuria; J. Samuel Kamanda; Eric Kwasi Elliason; Christian Gendemeh (International Journal of Behavioral Sciences, 2026)
Background: Burnout in healthcare professionals is described using the framework of Occupational Health and Resilience Theory, where self-care is an individual-level coping mechanism and institutional support is an organizational-level moderator. However, there is a lack of regional data from North India on the structural and contextual factors influencing burnout. Healthcare workers (HCWs) in North India face mounting pressures due to high patient loads, limited mental health resources, and overlapping professional and personal responsibilities. Understanding disparities in self-care, burnout, and institutional support is critical for informing policy and interventions. Objective: To examine self-care practices, burnout levels, and access to institutional support among HCWs across urban and rural settings in North India, with attention to gender and professional differences. . Methods: This cross-sectional study was conducted from January to December 2023 among 600 healthcare professionals in five states of North India using stratified random sampling. Burnout was measured using the Maslach Burnout Inventory, and self-care was measured using the WHO Self-Care Index. The institutional support variables included access to counseling services, mental health leave, and wellness activities. Institutional Review Board approval was taken (IEC/2022/45). The statistical analysis included effect size (Cohen’s d), odds ratio (OR), 95% confidence interval (CI), and multivariate regression coefficients (β). Data were analyzed using SPSS v28 with ANOVA and regression methods. Results: Urban healthcare professionals scored significantly higher on self-care (14.2 ± 3.1) than rural healthcare professionals (9.8 ± 2.7; p Conclusion: Burnout inequities in North India are a reflection of structural issues in gender and geographic disparities. Enhancing institutional support and incorporating resilience-focused occupational health policies in the national framework is essential for long-term workforce well-being.
Keywords: India; Self-care; burnout; gender disparities; healthcare workers; institutional support; rural-urban differences